Peningkatan Pengetahuan Keluarga Ibu Hamil Tentang Pencegahan Anemia Di Kota Bukittinggi - Diana Putri (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2025)
Anemia in pregnant women remains a major public health issue in Indonesia, including in Bukittinggi City. According to the Bukittinggi Health Office report in 2022, the prevalence of anemia among pregnant women reached 42%. This condition increases the risk of pregnancy complications such as bleeding, preterm delivery, low birth weight, and even maternal and infant mortality. Families play an essential role in supporting pregnant women, particularly in ensuring compliance with iron tablet consumption and providing nutritious food. This community service program aimed to improve family knowledge of anemia prevention through participatory health education. The methods included problem identification, focus group discussions, interactive education, simulation of nutritious meal planning, and accompaniment by community health cadres. The results showed a 35% increase in family knowledge based on pre- and post-test results. Furthermore, positive behavioral changes were observed, such as improved compliance with iron tablet consumption and the establishment of family support groups for pregnant women as new social institutions. This program demonstrated that participatory family-based education is effective in increasing knowledge and fostering social transformation for anemia prevention.